2021
DOI: 10.1021/acs.nanolett.0c05139
|View full text |Cite
|
Sign up to set email alerts
|

Probing Nanoscale Lipid–Protein Interactions at the Interface of Liquid Crystal Droplets

Abstract: Aqueous interfaces of liquid crystals (LCs) are widely explored in the design of functional interfaces to recapitulate the key aspects of biomolecular interactions in cellular milieu. Herein, using aqueous LC dispersions, we explore the interactions between mitochondrial cardiolipin and membrane-associated cytochrome c which play a pivotal role in the apoptotic signaling cascade. Conventional techniques used to decipher LC ordering at the droplet interface fail to give information about the interactions at a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Aqueous/LC interfaces thus provide a practical basis for the development of platforms for chemical and biomolecular sensing. Past studies have reported that micrometer-scale droplets of LC dispersed in aqueous phases (e.g., LC-in-water emulsions) provide a versatile approach for designing droplet-based sensors that can respond sensitively to the presence of a wide range of amphiphiles in aqueous environments. ,, These LC emulsions are straightforward to prepare and deploy and they enable real-time, label-free detection of toxins and other analytes with sensitivities that depend, in general, upon the concentration and structure of the analyte. As one important example, past studies demonstrate that LC emulsions can detect and report the presence of lipid A, a component of bacterial endotoxins, at concentrations as low as 1 pg/mL in water. , …”
Section: Introductionmentioning
confidence: 99%
“…Aqueous/LC interfaces thus provide a practical basis for the development of platforms for chemical and biomolecular sensing. Past studies have reported that micrometer-scale droplets of LC dispersed in aqueous phases (e.g., LC-in-water emulsions) provide a versatile approach for designing droplet-based sensors that can respond sensitively to the presence of a wide range of amphiphiles in aqueous environments. ,, These LC emulsions are straightforward to prepare and deploy and they enable real-time, label-free detection of toxins and other analytes with sensitivities that depend, in general, upon the concentration and structure of the analyte. As one important example, past studies demonstrate that LC emulsions can detect and report the presence of lipid A, a component of bacterial endotoxins, at concentrations as low as 1 pg/mL in water. , …”
Section: Introductionmentioning
confidence: 99%
“…Aqueous LC emulsions decorated with amphiphiles have been utilized for several applications. [24][25][26][27][28][29][30][31] LC molecules, when emulsified in water, exhibit a bipolar configuration where the LC molecules are aligned parallel to the droplet boundary. It has been reported that the adsorption of surfactants and other amphiphiles trigger a perpendicular ordering of LC to the droplet interface resulting in a radial configuration.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Abundant literature reports have focused on delineating the structure-property relationship of natural and synthetic amphiphiles with LC ordering and their subsequent applications in either sensing of analytes or understanding various interfacial phenomena. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Adsorption of amphiphiles at the aqueous-LC interface triggers changes in the LC orientation at the interface, which can be communicated over distances of up to 100 mm. These changes can be amplified into optical signals and visualized using a system of crossed polarizers.…”
Section: Introductionmentioning
confidence: 99%
“…To learn more about molecular interactions at the droplet interface, Pani et al [ 109 ] employed aqueous LC dispersions to investigate the interaction between mitochondrial cardiolipin (CL) and membrane-associated cytochrome c (Cyt c) (the latter of which is essential for the apoptotic signaling cascade). The CL wrapped around the surface of 5CB droplets and bound to Cyt c at the droplet surface in an aqueous phase environment ( Figure 6 ).…”
Section: Overview Of Lc Droplet-based Biosensors For Poc Diagnosis Of...mentioning
confidence: 99%